Pope Benedict XII (1334-1342) : the guardian of orthodoxy - Bueno, Irene (Church, faith, and culture in the Medieval West., 2018)
The essential aim of this series is to present high quality, original, and international scholarship, covering all aspects of the Medieval Church and its relationship with the secular world in an accessible form. Previous publications have covered such topics as aspects of Medieval Papal History, including neglected twelfth- and thirteenth-century popes, Monastic and Religious Orders for men and women, Canon Law, Liturgy and Ceremonial, Art, Architecture and Material Culture, Ecclesiastical Administration and Government, as well as aspects of Clerical Life, Councils and so on. Our authors are encouraged to challenge existing orthodoxies on the basis of thorough examination of relevant sources.